Effect of microencapsulation on antioxidant activities of Eugenia punicifolia (Kunth) DC hydroethanolic extracts - Martins, Manoela (2024)
Eugenia punicifolia (Kunth) DC (Myrtaceae) is a folk medicinal plant in the Brazilian Cerrado with antioxidant, anti-inflammatory, antinociceptive, antiulcerogenic activities, etc., usually attributed to its phenolic compounds. Since these compounds are sensitive to heat and light, and to increase their applications, Hydroethanolic Extracts E. punicifolia (HEEP, EtOH:H2 O 70% v/v) were encapsulated by freeze-drying in xanthan gum (mesh 80, HEEPX80; mesh 200, HEEPX200) in ratio 1:1(w/w). Flavonoids had the highest encapsulation efficiency in HEEPX80, with a total flavonoid content of 55.56%. The release profile at different pH levels showed that pH = 4.5, a relevant antioxidant activity for HEEPX80 and HEEPX200. Also, in HEEP-modified release, higher antioxidant activity was observed in more acidic media (pH 4.5) than in a more neutral medium (pH 7.4). From these results, we could infer that HEEP encapsulations with Xanthan gum could be a good alternative for preserving antioxidants in these extracts.